Simultaneous Bilateral Femoral Neck Stress Fracture in a Young Stone Mason - Nikhil A. Khadabadi; Kiran S. Patil (Case Reports in Orthopedics)
Unilateral stress fractures of the femoral neck are very uncommon and bilateral involvement is even rarer. They commonly occur in athletes, military recruits, older persons, or individuals with underlying metabolic disorders and very seldom in normal individuals. We present a rare case of simultaneous bilateral fracture neck of femur in a 25-year-old man who came with complaints of pain in bilateral groin for 1 month. There was no history of trauma or history suggestive of excessive activity prior to the onset of pain, but there was history of lifting heavy weights daily. On evaluation with MRI scan bilateral fracture of the femur neck was diagnosed and patient was operated on bilaterally with internal fixation done using dynamic hip screw. Patient then regained his routine activity over a period of 6 months and on follow-up at 1 year no avascular necrosis changes were seen in the femur head. We presented this case because of its unusual presentation and the diagnostic challenge it poses.